2021
DOI: 10.1155/2021/2366709
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation on Initiation and Propagation of Hydraulic Fractures in Shale Reservoir

Abstract: Hydraulic fracturing is a necessary technique for shale gas exploitation. In order to have efficient stimulation treatment, a complex fracture network has to be developed, whereas with rich bedding planes and natural fractures, the mechanism of forming a fracture network is not fully understood and it is so tricky to predict propagation and initiation of hydraulic fracture. Therefore, in this paper, considering the strong anisotropy of shale reservoir, numerical simulation has been conducted to analyze fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…(1) Currently, physical simulation experiments and numerical simulation techniques are often used to study the propagation mechanism of hydraulic fractures. Among them, the indoor physical simulation experimental method uses small-sized rock samples for hydraulic fracture tests, which simulates the fracturing operation process at the subsurface reservoir scale indoors and can reflect the propagation of hydraulic fractures during the fracturing process in a simple and intuitive way [58,60,144,165]. In addition, indoor physical model experiments can be used to explore the influence of one or some parameters on the hydraulic fracture propagation pattern and to analyze the main control factors affecting the fracture propagation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Currently, physical simulation experiments and numerical simulation techniques are often used to study the propagation mechanism of hydraulic fractures. Among them, the indoor physical simulation experimental method uses small-sized rock samples for hydraulic fracture tests, which simulates the fracturing operation process at the subsurface reservoir scale indoors and can reflect the propagation of hydraulic fractures during the fracturing process in a simple and intuitive way [58,60,144,165]. In addition, indoor physical model experiments can be used to explore the influence of one or some parameters on the hydraulic fracture propagation pattern and to analyze the main control factors affecting the fracture propagation.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the results of both studies, it was found that the simulation results did not completely match the experimental results and there were some errors. In addition, the cementation strength of the laminae [82,112,[144][145][146] has an important influence on the hydraulic fracture propagation. Shales with high cementation strength will hinder the longitudinal propagation of fractures, while shales with weak cementation strength tend to propagate along the laminae, i.e., too strong or too weak cementation strength of laminae is not conducive to the formation of complex fracture networks, and the dip angle of laminae also has a certain influence on the propagation of hydraulic fractures.…”
Section: Geological Factormentioning
confidence: 99%
“…Enhanced oil recovery (EOR) methods employ diverse approaches to maximize production. However, current techniques have limitations. Chemical EOR using surfactants and polymers risks environmental damage. CO 2 injection raises concerns about greenhouse gas emissions. Mechanical fracking poses threats like induced seismicity, water contamination, and strain on local resources. Thermal techniques like steam injection and in situ combustion leverage heat to improve oil mobility and reduce viscosity. …”
Section: Introductionmentioning
confidence: 99%
“…to form in shales with high brittle mineral contents under hydraulic fracturing, and these generally extend along the boundaries between hard mineral grains and soft organic matter [28,29]. The fracturing mechanism, fracture extension characteristics, and spatial distribution under hydraulic fracturing are investigated by a true triaxial fluid-solid coupling test system [30] and numerical tests [31][32][33], which lead to the conclusion that the induced fractures mainly extend along natural fractures and laminar surfaces [34,35]. In recent years, many studies have performed and laid a solid cornerstone in the area of hydraulic fracture modification [36].…”
Section: Introductionmentioning
confidence: 99%